KONTEKS MODERASI MAKKI MADANI DAN NASAKH MANSUKH - Khoirur Rozikin; Muhammad Farih (Makkah: Journal Of Islamic Studies, 2026)
Abstract : This article examines the context of moderation in the Qur’an through a comprehensive analysis of two key concepts in ‘Ulūm al-Qur’ān, namely the Makki-Madani classification and Nasakh-Mansukh. These two concepts serve as an epistemological framework that emphasizes that the revelation of the Qur’an took place gradually and was responsive to social changes in Arab society in the early Islamic period. Using a qualitative-descriptive research method based on literature study, this article examines the historical, thematic, and linguistic characteristics of Makki and Madaniyah verses, and examines the principles, conditions, and differences in the views of scholars regarding the concept of nasakh. The results of the study indicate that Makkiyyah verses serve to build theological, moral, and spiritual foundations, while Madaniyyah verses regulate the social and legal structures of established Muslim societies. Meanwhile, the Nasakh–Mansukh concept illustrates the flexibility of Islamic law through a progressive and contextual mechanism for legal refinement. Both concepts emphasize the principle of Islamic moderation, which balances universal values ​​and the practical needs of society. The conclusion is that a moderate and contextual understanding of Makkiyyah–Madani and Nasakh–Mansukh is crucial in developing a methodology for interpreting the Qur'an that is relevant to contemporary religious and social challenges. These findings are expected to enrich postgraduate interpretation studies and contribute to strengthening the discourse on religious moderation in Indonesia.